2020
DOI: 10.1590/2177-9465-ean-2020-0027
|View full text |Cite
|
Sign up to set email alerts
|

Saúde do trabalhador no contexto da estratégia de saúde da família: revisão integrativa de literatura

Abstract: RESUMO Objetivo Identificar a produção de conhecimento sobre a Saúde do Trabalhador na Estratégia de Saúde da Família (ESF), com base na literatura científica nacional. Método Revisão integrativa de literatura. A busca foi realizada em outubro de 2019 e atualizada em abril de 2020, nas seguintes bases de dados: Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS) e Scientific Electronic Library Online (SciELO), por meio do portal da Biblioteca Virtual em Saúde (BVS). Resultados Foram encont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
3
0
6
Order By: Relevance
“…In line with this finding, a study carried out with primary care health workers showed that workers’ mental health is directly affected by the conditions of the place where they work. Among the various problems, depression, anxiety and burnout syndrome were the most common ( 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In line with this finding, a study carried out with primary care health workers showed that workers’ mental health is directly affected by the conditions of the place where they work. Among the various problems, depression, anxiety and burnout syndrome were the most common ( 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Estudos publicados após a coleta de dados desta revisão, apontam persistência de contradições mencionadas. Por exemplo, na dimensão da integralidade (contradição 3: assistência e vigilância), Faria et al 67 indicam que a inserção da linha de cuidado da ST na Estratégia de Saúde da Família ainda é frágil. Os autores alertam, igualmente, que estão ocorrendo transformações importantes no campo da Política Nacional de AB e na capacidade do Estado em garantir a seguridade social dos trabalhadores, e que é necessário defender o direito a políticas públicas para a classe trabalhadora.…”
Section: Discussionunclassified
“…Studies which were published after the data collection for this review indicate a persistence of the contradictions mentioned here. For instance, in the integrality dimension (contradiction 3: assistance and surveillance), Faria et al 67 indicated that the insertion of the line of WH care in the Family Health Strategy is still weak. The authors also warn that important transformations are happening in the field of national PHC policies and in the ability of the State to guarantee the workers' social security, which is necessary to fight for the right to have public policies for the working class.…”
Section: Discussionmentioning
confidence: 99%